2009
DOI: 10.1016/s0140-6736(09)61674-3
|View full text |Cite
|
Sign up to set email alerts
|

Rates of virological failure in patients treated in a home-based versus a facility-based HIV-care model in Jinja, southeast Uganda: a cluster-randomised equivalence trial

Abstract: SummaryBackgroundIdentification of new ways to increase access to antiretroviral therapy in Africa is an urgent priority. We assessed whether home-based HIV care was as effective as was facility-based care.MethodsWe undertook a cluster-randomised equivalence trial in Jinja, Uganda. 44 geographical areas in nine strata, defined according to ratio of urban and rural participants and distance from the clinic, were randomised to home-based or facility-based care by drawing sealed cards from a box. The trial was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
277
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(291 citation statements)
references
References 26 publications
11
277
3
Order By: Relevance
“…A meta-analysis of 18 cohort studies conducted by Sterne et al (2009) under the "When to Start Consortium" also confirmed that early initiation of ART is associated with increased survival rates. The findings of this study are, however, inconsistent with those of the Ugandan Cluster Randomised Trial of 300 HIV infected children (1-12 years], which revealed that survival and growth of children who were early initiated (CD4% > 15) on ART compared to those who were delayed (CD4% ≤ 15) ART was not different (Jaffar et al, 2009). Similarly, a prospective study conducted by Kipp et al (2010) revealed that early initiation on ART had poor survival benefits among children 2-5 years old.…”
Section: Discussioncontrasting
confidence: 99%
“…A meta-analysis of 18 cohort studies conducted by Sterne et al (2009) under the "When to Start Consortium" also confirmed that early initiation of ART is associated with increased survival rates. The findings of this study are, however, inconsistent with those of the Ugandan Cluster Randomised Trial of 300 HIV infected children (1-12 years], which revealed that survival and growth of children who were early initiated (CD4% > 15) on ART compared to those who were delayed (CD4% ≤ 15) ART was not different (Jaffar et al, 2009). Similarly, a prospective study conducted by Kipp et al (2010) revealed that early initiation on ART had poor survival benefits among children 2-5 years old.…”
Section: Discussioncontrasting
confidence: 99%
“…41,42 Moreover, community interventions are not necessarily more expensive if delivered by supervised community workers. 43 …”
Section: Prevention Of Tuberculosis With the 3ismentioning
confidence: 99%
“…In addition, a home-based HIV care strategy in Uganda using lay health workers was found to be as effective as a clinic-based strategy on viral suppression after six months of ART (Jaffar et al 2009). The benefits observed in these studies may be because CHWs can help to demystify HIV, counteract stigma and act as a bridge between the community and the health facility (Mwai et al 2013).…”
Section: Theory Of Changementioning
confidence: 99%